2021
DOI: 10.51507/j.jams.2021.14.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electroacupuncture Therapy on Pain, Plasma β-Endorphin, and Quality of Life of Stage III Cervical Cancer Patients: A Randomized Control Trial

Abstract: Background: Pain is a major complaint in cancer patients and a global problem that requires medical attention, including pain in cervical cancer. Although pharmacotherapy has been used for the treatment of cancer pain, there are still around 40% cannot be treated only with pharmacotherapy. Objectives: To determine the effects of electroacupuncture (EA) on pain in stage III cervical cancer patients. Methods: Twenty-eight stage III cervical cancer patients were divided into two groups (14 treatments and 14 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Zusanli (ST36), Hegu (LI4), Sanyinjiao (SP6), and the extraordinary point Siguan were the most frequently used acupoints. Eleven studies reported “deqi” ( 21 , 23 – 26 , 29 – 32 , 34 , 36 ), a sensation of needling perceived as soreness, numbness, or distension, which is usually achieved by manipulating acupuncture needles to obtain the desired therapeutic effect, and seven other studies did not mention this effect ( 20 , 22 , 27 , 28 , 33 , 35 ). In most studies, patients were treated for 30 min per session.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Zusanli (ST36), Hegu (LI4), Sanyinjiao (SP6), and the extraordinary point Siguan were the most frequently used acupoints. Eleven studies reported “deqi” ( 21 , 23 – 26 , 29 – 32 , 34 , 36 ), a sensation of needling perceived as soreness, numbness, or distension, which is usually achieved by manipulating acupuncture needles to obtain the desired therapeutic effect, and seven other studies did not mention this effect ( 20 , 22 , 27 , 28 , 33 , 35 ). In most studies, patients were treated for 30 min per session.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of time patients received electroacupuncture treatment ranged from 1 to 12 weeks. In terms of electroacupuncture waveforms, six studies used disperse dense wave ( 20 , 26 , 27 , 33 – 35 ), four studies used continuous waves ( 30 – 32 , 36 ), and one study used only dense waves ( 28 ), with the remaining trials not specified; in terms of electroacupuncture frequency, it ranged from 2 hz to 100 hz, in terms of applying electroacupuncture current intensity, only a few studies specifically reported the intensity of the current used ( 27 , 31 , 35 , 36 ), most of the other trials stated the maximum intensity within the patients’ tolerance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations